KAJIAN TENTANG PERBAIKAN KUALITAS CITRA DALAM AIR MENGGUNAKAN METODE DARK CHANNEL PRIOR - Edi Putra; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Digital image processing is a branch of engineering informatics. image processing is an attempt to change your photo or image into another by using certain techniques. The process of changing the image data into digital data by using a computer known as digital image processing. The purpose of this application is to improve the image quality of the water using test images and imagery training, to train image by image is in the water, while the test images by using the image processing Dark Channel Prior. The image that was in the sea water murky and foggy be processed and then do a comparison with the image that is not in the water. The design is made in the form of software applications to improve the quality of the image using the Dark Channel Prior. In this study, created by using Visual Basic 2013.